Geotechnical characterisation of zinc tailing waste material for road construction. Issue 6 (2nd November 2022) - Sinha, Anil Kumar; Havanagi, Vasant G.; Sreekantan, Parvathi Geetha; Chandra, Satish
ABSTRACT: Zinc tailing waste material is generated during the extraction of zinc metal. Its deposit is increasing year after year posing a threat to the environment and occupying large precious land. The present research explores the possibility of its application in road construction and filling. Physical and chemical tests were carried out, viz. SEM, EDS, X-ray diffraction and toxicity characteristics leachate procedure. The geotechnical characterisation was carried out and compared with similar types of materials, viz. soil and industrial wastes (fly ash and jarofix). Stress-settlement behaviour was studied by using a small scale physical model and validated by a numerical model test. Tailing was further mixed with cement to improve its properties for application in stabilised layers. Tailing is a porous, multi-phase and non-swelling cohesionless fine-grained material. It contains mainly oxides of silica, alumina, magnesium, calcium and less concentration of heavy metals. It has a high dry density (18.62 kN/m 3 ), California Bearing Ratio (11%) and angle of internal friction (34°) compared to soil which makes it suitable for road construction. Cement stabilised tailing can be used in sub-base layer and can save about 170 mm thickness of the aggregate layer. Modulus value (18.17 MPa) indicates that it is a stiff material which leads to less settlement as a structural fill.